WOX11 recruits a histone H3K27me3 demethylase to promote gene expression during shoot development in rice. Issue 5 (18th January 2018) - Cheng, Saifeng; Tan, Feng; Lu, Yue; Liu, Xiaoyun; Li, Tiantian; Yuan, Wenjia; Zhao, Yu; Zhou, Dao-Xiu
Abstract: WUSCHEL-related homeobox (WOX) genes are key regulators of meristem activity and plant development, the chromatin mechanism of which to reprogram gene expression remains unclear. Histone H3K27me3 is a chromatin mark of developmentally repressed genes. How the repressive mark is removed from specific genes during plant development is largely unknown. Here, we show that WOX11 interacts with the H3K27me3 demethylase JMJ705 to activate gene expression during shoot development in rice. Genetic analysis indicates that WOX11 and JMJ705 cooperatively control shoot growth and commonly regulate the expression of a set of genes involved in meristem identity, chloroplast biogenesis, and energy metabolism in the shoot apex. Loss of WOX11 led to increased H3K27me3 and overexpression of JMJ705 decreased the methylation levels at a subset of common targets. JMJ705 is associated with most of the WOX11-binding sites found in the tested common targets in vivo, regardless of presence or absence of the JMJ705-binding motif. Furthermore, wox11 mutation reduced JMJ705-binding to many targets genome-wide. The results suggest that recruitment of JMJ705 to specific developmental pathway genes is promoted by DNA-binding transcription factors and that WOX11 functions to stimulate shoot growth through epigenetic reprogramming of genes involved in meristem development and energy-generating pathways.